(untitled) (Journal of the College of Basic Education, 2022)
Art in general has an important role in building societies, as it is like a mirror that reflects the culture and opinions of individuals. The art of murals is one of the historical evidence of the relationship of individuals and societies over time. The current research dealt with the figurative creation between sculptural and mural forms in contemporary Iraqi ceramics. Is the pictorial form of the mural or the madrasah, the formulations and formal treatments related to the subject and the idea in contemporary Iraqi art?; And the importance of the research, which lies in revealing the formulation of formal systems and the aesthetic effect of the material and the mechanism of its employment in the pictorial construction between the sculptural and mural forms in contemporary Iraqi ceramics, and the aim of the research is to reveal the figurative construction in contemporary Iraqi ceramic works between stereoscopic and mural forms and the limits of the research that were confined between 1974 – 2010, The research also dealt with some keywords related to the research; As for the second chapter, it included two sections, the first dealt with the figurative construction and its elements. The second topic was of two axes, the first of which is the sculptural ceramic figure and the second is the wall ceramic. The chapter ends with some indicators that resulted from the theoretical framework. As for the third chapter, it represented the procedures of research and analysis of samples that were divided into two groups, namely, stereoscopic shapes. And the wall hangings, and the research ended with the fourth chapter, which represented some of the results, recommendations and suggestions reached by the researcher.